2018
DOI: 10.1002/andp.201800116
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Electromagnetic‐Wave‐Absorbing Performance of a Broadband Four‐Layer Absorbing Composite

Abstract: A four-layer absorbing composite on millimeter scale is designed containing an absorbent with multilayer-like structure on the microscale. In this four-layer absorbing composite, epoxy resin acts as transparent layer, the multilayer-like structure absorbent serves as the main absorbing layer; graphene/Ni composite acts as an impedance matching layer; and Fe 3 O 4 nanoparticles serve as a magnetic-loss absorbing layer. The reflection loss of the composites is simulated with CST Microwave Studio, and the absorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Therefore, the values of h r and a for the single-layer foamed graphene/TPU composites with different foam ratios were calculated by eqn (13) and (14) and the results are demonstrated in Fig. 6a and b.…”
Section: Ew-absorbing Properties Of Single-layer Graphene/tpu Composimentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the values of h r and a for the single-layer foamed graphene/TPU composites with different foam ratios were calculated by eqn (13) and (14) and the results are demonstrated in Fig. 6a and b.…”
Section: Ew-absorbing Properties Of Single-layer Graphene/tpu Composimentioning
confidence: 99%
“…Polymeric composites, owing to their exibilities for structure design and property modulation, light weight, and good processability, have been widely used in the design and implementation of EWAMs. [4][5][6] Dielectric absorbents, such as carbon nanotubes (CNTs), [7][8][9] carbon bers (CFs), 10,11 and graphene and its derivatives, [12][13][14] due to their light weight, high conductivity, high aspect ratio, good resistance against corrosion, and excellent mechanical properties [15][16][17][18] have been added into polymer matrixes to achieve EW-absorbing properties. The most important features of these absorbents are their strong absorption capacity (reection loss, RL) and broad effective absorption bandwidth (EB, RL < À10 dB, for 90% energy absorption).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, serious electromagnetic radiation caused by the prompt development of wireless communication and electronic technologies has made the urgent requirement for highly effective microwave absorbers. Heterogeneous structures in microwave absorbing materials that can integrate the distinct loss mechanisms of multi-components have attracted widespread attention in the design of highly effective microwave absorbers. , Moreover, stronger interfacial polarization with better impedance matching has been confirmed in microwave-absorbing materials designed with multiple heterostructures and components for enhanced electromagnetic wave absorption properties. For example, Bao and co-workers report a heterogeneous-structured FeCo/ZnO nanosheets with excellent impedance matching. Wang et al improved microwave-absorbing properties of Mo@2D-MoS 2 by introducing heterogeneous interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The percolative composites with high permittivity (ε') are simply achieved by increasing the fraction of fillers to the percolation threshold, at which the dielectric constant is abruptly improved. [9,10] For example, Grannan et al reported the Ag/KCl composites which exhibited a much higher dielectric constant than pure KCl (about 10 times higher), attributing to the significant blocking of charge carries at internal interfaces. [11] Percolative composites with high permittivity (ε') and low loss (tanδ) exhibit wide range of application in sensors, capacitors, field-effect transistors, antennas, etc., drawing enormous attention in the research community.…”
Section: Introductionmentioning
confidence: 99%